БОШЛАНҒИШ СИНФ ЎҚИТУВЧИЛАРИНИ ИННОВАЦИОН ФАОЛИЯТГА ТАЙЁРЛАШ ТИЗИМИНИ ТАКОМИЛЛАШТИРИШНИНГ НАЗАРИЙ АСОСЛАРИ - Салиева, П.А. (SCIENCE and SOCIETY, 2022)
As the issue of education has become the priority of our state policy, the time demands that our pedagogues have a new approach to the ultimate goals. Because only highly qualified specialists are responsible for the people and society in order to prepare the young generation for life and defense of the Motherland. is a responsible person engaged in the work of giving.
Keywords: education; professional skills; self-development; professional competence; quality and effectiveness of education